Pengaruh Posisi Skarifikasi Benih dan Perendaman Air Kelapa terhadap Perkecambahan Biji dan Pertumbuhan Bibit Sirsak (Annona muricata L.) - Arya Agung Pranata; Asil Barus; Meiriani (Jurnal Pertanian Tropik, 2018)
The problem of generative propagation of soursop is its seeds take a long time to germinate which are caused by the hard seed coat. The solution to solve that problem is scarification and coconut water soaking to simply the process of imbibition and seed germination and also stimulate the growth of shoot. This objective of the research was to determine the effect of the scarification position and the soaking with various concentrations of coconut water on seed germination and growth of soursop seedling. This research was held at the Faculty of Agriculture field, the University of Sumatera Utara in March - July 2017. The research used a factorial randomized block design with two factors and three replication. The first factor is the scarification position (without scarification, stomach scarification, top scarification) and the second factor is coconut water soaking (0%; 25%; 50%; 75 %). The result of the research showed that the germination rate parameter, germination percentage, crop height, number of leaves, root volume and dry weight of crop significantly higher on without scarification treatment than with scarification treatment. The interaction between the scarification position and soaking with various coconut water concentrations was not significantly affecting the seed germination and growth of soursop seedling.